Maternidade e vida acadêmica: um estudo sobre os desafios enfrentados por estudantes universitárias mães do Campus da UFPA em Castanhal - SILVESTRE, Débora Lameira (2019)
This paper aims to analyze the challenges faced by mother university students, in order to understand how such students reconcile motherhood with the demands of the university world. The choice of this theme arose from the observation of women who even pregnant or having to take their children to university continued to study. And, seeking to answer this question, we conducted a qualitative approach investigation, having as data collection instruments, form on women and maternity, demanded for the Colleges of Castanhal Campus; Interviews with five (05) women between 19 and 26 years old who were mothers during the academic course. The locus was the University Campus of Castanhal / UFPA. The authors who favor the dialogue about Women, Maternity, Education were: Elizabeth Badinter (1985), Nancy Chodorow (2002), Laurel (1997) Sampaio (2008), (Urpia 2009), Coulon (2009) among others. The results in the dialogue with the literature on women and motherhood indicate that, for a long time, women were seen as inferior, unable to play any role other than devoting themselves to private life and reproduction. Moreover, motherhood was surrounded by restrictions on women, and at no given historical moment one wants to breastfeed her child. The data show that the limitations imposed on the female figure left women without education, for a long time, but gradually, with historical struggles conquered access to schooling, reaching higher education, gaining its place as a subject of rights. As well as, the results of the data indicate that the difficulties encountered by the university students / mothers correspond to the responsibilities related to the exercise of the double function, where the experience of the challenge and the journey was only possible due to the unconditional support they receive from their mothers.